PENGARUH JARAK DAN LAMA WAKTU PROSES PENGHITUNGAN STRAW SEBELUM DISTRIBUSI TERHADAP KUALITAS SEMEN BEKU SAPI SIMENTAL POST THAWING - Fatimah, Siti Nur; Wurlina, Wurlina; Wahjuni, Retno Sri (Universitas Airlangga, 2018)
Aims of this research was to determine the effect of distance and the duration of straw count above liquid nitrogen to the Quality of Frozen Simental Cattle. This study used a sample derived from simmental cattle from BBIB singosari as much as 48 straw divided into 8 treatments. P1(0,5cm 15 sec), P2(0,5cm 30 sec), P3( 0,5cm 45 sec), P4(0,5cm 60 sec), P5(1,5cm 15 sec), P6(1,5cm 30 sec), P7(1,5cm 45 sec), P8(1,5cm 60 sec) and repeated as much as 6 times then observed for motility and viability of post thawing spermatozoa. The data obtained were analyzed using SPSS 16.0. The data obtained were analyzed using SPSS 16.0. The results showed that the duration of straw count and the position of straw from liquid nitrogen not significant (P>0,05) on post thawing motility. The position of straw from liquid nitrogen not signifant (P>0,05) on post thawing viability. The conclusion of this research showed that 0,5 cm 15 sec give the higher post thawing motility.